Influence of carbonation on ionic transport in unsaturated concrete: evolution of porosity and prediction of service life. Issue 5 (4th May 2019) - Achour, Mohamad; Amiri, Ouali; Bignonnet, François; Roziere, Emmanuel
Abstract: In this paper, the effects of carbonation and moisture on chloride and ionic transport into concrete are studied. Based on the concrete composition and porosity as well as the physicochemical equilibrium, a comprehensive macroscopic model is proposed for this problem. The model features the chemical activity of ions, the interactions between chloride ions and concrete; and the ion–ion interactions in the solution. The governing equations of moisture and ionic transport into nonsaturated concrete are thoroughly described and solved numerically by the finite difference method in time and in space. Applications of the numerical model are demonstrated by predicting the evolution of the porosity and the service-life of a concrete specimen exposed to an aggressive environment containing chloride, carbon dioxide and moisture. A comparison of the model with a set of experimental data is finally proposed.